Comparative incidence of rejection occurring in small intestinal and colonic mucosal biopsies of patients undergoing intestinal transplantation. Issue 4 (21st June 2016) - Huard, Geneviève; Schiano, Thomas; Fiel, Marie I; Ward, Stephen C; Moon, Jang; Iyer, Kishore
Abstract : Aims: To compare the diagnosis of acute cellular rejection (ACR) based on biopsies (Bx) performed simultaneously in the small bowel (SB) and colonic grafts (paired Bx) after intestinal transplantation (ITx). Methods and results: Retrospective study including all ITx with colon at Mount Sinai Hospital between 2009 and 2014. Paired Bx were reviewed blindly by two experienced gastrointestinal (GI) pathologists and were graded based on the VIII International Small Bowel Transplant Symposium Consensus criteria, with minor modifications for evaluation of colon biopsies. Each Bx was classified as negative or positive for ACR. Cohen's kappa statistic was used to quantify the interpathologist agreement and the agreement between SB and colonic Bx for the diagnosis of ACR. Fifteen patients underwent 51 paired Bx. The strength of agreement for the grade of ACR in the SB biopsies (kappa = 0.62) and the colonic biopsies (kappa = 0.65) was good. The inter‐rater agreement was better for Bx negative for ACR and for higher grades of ACR. Overall, 74.5% of paired Bx were concordant for the presence or absence of ACR. The strength of agreement for the presence or absence of ACR between the SB and colonic Bx (kappa = 0.44) was moderate. Two cases of severe ACR were restricted to the SB allograft. Conclusions: Paired Bx in the SB and the colon are usually in agreement regarding the presence or the absence of ACR. However, colonic Bx alone may not suffice to exclude ACR following ITx. With minor modifications, the histopathological criteria of the SB may be adaptable to the colonic allograft.